Augmented Reality Sebagai Media Pelatihan Penanganan Kebakaran Hutan Bagi Warga Desa Pasir Panjang Batam - Ahmad Hamim THohari; Hamdani Arif; Dwi Ely Kurniawan; Muchammad Fajri Amirul Nashrullah; Maidel Fani; Nelmiawati Nelmiawati; Heru Wijanarko; Rizky Pratama Hudhajanto; Rina Yulius; Mira Chandra Kirana; Uuf Brajawidagda; Muhammad Nashrullah; Nur Cahyono Kushardianto; Dodi Prima Resda; Finkye Priya Gunadi (Pusat P2M Politeknik Negeri Batam, 2021)
The dry season in Batam brings the threat of drought. The dry season has an impact in the form of the threat of fires in settlements and protected forests in the Rempang and Galang Islands, Batam. Based on the survey and analysis activities in 2018, it is known that residential areas in Pasir Panjang Village often experience fires, however, residents do not yet have the knowledge and ability to handle early fire disasters. In the 2018 community service activities, socialization was carried out with the Batam City Fire Service, but it had not yet reached the technical realm. Fire handling training is required for residents with fire extinguishers, however, residents' access to this tool is still limited and the price is quite expensive. This activities has produced an application prototype based on augmented reality to simulate the use of a fire extinguisher as a media for educating citizens. The application prototype has been tested and can serve as a training medium for residents. In addition, this community service program also provides training and assistance in handling in a fire disaster.